Cfengine. a step-by-step guide to setting up CFEngine and fully automating the configuration and management of your laptop, desktop, server, or mainframe /: a step-by-step guide to setting up CFEngine and fully automating the configuration and management of your laptop, desktop, server, or mainframe. 3 beginner's guide : (2011) - Unknown
No abstract available